First Long-term Oncologic Results of the ALPPS Procedure in a Large Cohort of Patients With Colorectal Liver Metastases. Issue 5 (November 2020) - Petrowsky, Henrik; Linecker, Michael; Raptis, Dimitri A.; Kuemmerli, Christoph; Fritsch, Ralph; Kirimker, Onur E.; Balci, Deniz; Ratti, Francesca; Aldrighetti, Luca; Voskanyan, Sergey; Tomassini, Federico; Troisi, Roberto I.; et al.
Abstract : Objectives: To analyze long-term oncological outcome along with prognostic risk factors in a large cohort of patients with colorectal liver metastases (CRLM) undergoing ALPPS. Background: ALPPS is a two-stage hepatectomy variant that increases resection rates and R0 resection rates in patients with primarily unresectable CRLM as evidenced in a recent randomized controlled trial. Long-term oncologic results, however, are lacking. Methods: Cases in- and outside the International ALPPS Registry were collected and completed by direct contacts to ALPPS centers to secure a comprehensive cohort. Overall, cancer-specific (CSS), and recurrence-free (RFS) survivals were analyzed along with independent risk factors using Cox-regression analysis. Results: The cohort included 510 patients from 22 ALPPS centers over a 10-year period. Ninety-day mortality was 4.9% and median overall survival, CSS, and RFS were 39, 42, and 15 months, respectively. The median follow-up time was 38 months (95% confidence interval 32–43 months). Multivariate analysis identified tumor-characteristics (primary T4, right colon), biological features ( K/N-RAS status), and response to chemotherapy (Response Evaluation Criteria in Solid Tumors) as independent predictors of CSS. Traditional factors such as size of metastases, uni versus bilobar involvement, and liver-first approach were not predictive. When hepatic recurrences after ALPPS was amenable to surgical/ablative treatment, median CSS was significantly superior compared to chemotherapy alone (56 vs 30 months, P < 0.001). Conclusions: This large cohort provides the first evidence that patients with primarily unresectable CRLM treated by ALPPS have not only low perioperative mortality, but achieve appealing long-term oncologic outcome especially those with favorable tumor biology and good response to chemotherapy. Abstract : Supplemental Digital Content is available in the text